18 High levels of anxiety and depression in patients attending with headaches to a UK general neurology clinic. (28th May 2019) - Cronin, Thomas; Pearce, Ronald
Abstract : Objective: The published literature on headache epidemiology comes from specialist headache clinics, compared to the general neurology clinic. This study set out to investigate the characteristics and diagnoses of patients with headaches attending a general neurology clinic in the UK. Methods: Data were collected retrospectively from a two-year period on 217 patients with headaches referred to a general neurology clinic at a UK district-general hospital seen by a single consultant. Clinic letters were reviewed, and information was inputted using a pre-formed Microsoft Excel spreadsheet. All data were anonymised, with no identifiable patient characteristics being recorded. Results: A total of 217 were seen in this period. The mean age was 42% and 72% were female. In 56% of cases, more than one diagnosis was made. The most frequent diagnosis was migraine (72%), followed by tension-type headache (56%). Dizziness and/or vertigo was a commonly reported co-existing symptom, with 24% reporting this. For 13% (n=29) of cases, it was documented that time was taken out of work or studies due to headache symptoms. In 205 patients it was reported whether sleep was affected, with 70% (n=144) of cases indicating it was. For 195 cases, 80% (n=155) reported a normal appetite, 16% (n=32) a decrease, and 4% (n=8) an increase in appetite. In 195 patients, 65% (n=126) reported reduced energy levels. For 21% (n=46) there was documentation of anxiety. Regarding mood, in 176 cases where this was recorded, 33% gave a negative mood description. Conclusion: To the authors' knowledge, this study is the first to report on headache characteristics in patients presenting to a UK general neurology clinic. The diagnostic frequency of different headaches presented in this study are comparable to those described in specialist headache clinics. Our population demonstrate significant psychiatric morbidity associated with headaches, with 33% reporting negative mood value and in addition higher proportions reporting energy and sleep disturbance. To conclude, this study has shown the common headache diagnoses encountered in a general neurology clinic, and indeed is comparable to headaches managed in primary care. Improved integration between these services is key to ensuring effective care for such patients.